(untitled) (Journal of Engineering, 2017)
Flexible pipes, such as GRP pipes, serve as effective underground infrastructure especially as sewer pipeline. This study is an attempt for understanding the effects of bedding types on the behavior of large diameter GRP flexible sewer pipes using three dimensional finite element approaches. Theoretical and numerical analyses were performed using both BS EN 1295-1 approach and finite element method (ABAQUS software). The effects of different parameters are studied such as, depth of backfill, bedding compaction, and backfill compaction. Due to compaction, an increase in the bedding compaction modulus (E’1) results in a reduction of both stresses and displacements of the pipe, especially, for well compacted backfill. An increase of (E’1) from 14MPa to 30MPa results in a reduction in stresses 40% and about 25% in displacements. Maximum reductions in stresses were found to be about 25% only while the reduction in displacement was found to be less than 10%. As backfill material compaction modulus (E’2) is increased from 14MPa to 40MPa, a maximum reduction in stresses within the pipe was found to be not less than 60% while the displacement reduces up to 65%.